The Strategic Role Of Job Satisfaction In Improving Employee Performance Through Strengthening Motivation (A Study Of Private Banking In Bandung City - Abdul Azis; Zulganef Zulganef (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the influence of work motivation on employee performance with job satisfaction as a mediating variable among frontliners at Bank OCBC NISP in Bandung. The background of this study is based on the fluctuations in frontliner performance in achieving monthly targets, which indicates the importance of internal factors such as motivation and job satisfaction in supporting the achievement of optimal performance. This study uses a quantitative method with an explanatory research approach. A sample of 141 respondents was selected proportionally from a population of 218 frontliners. The data analysis technique used is path analysis with the help of SPSS software. The results show that work motivation has a positive and significant effect on employee job satisfaction and performance. Job satisfaction also has a significant effect on performance. The Sobel test shows that job satisfaction significantly mediates the relationship between motivation and employee performance. These findings indicate that increasing work motivation, both through financial and non-financial incentives, must be accompanied by the creation of a supportive work environment to achieve optimal levels of satisfaction and performance. This study provides practical implications for banking management in designing strategies to increase employee productivity through motivational approaches and job satisfaction.